2021
DOI: 10.1002/jmv.26794
|View full text |Cite
|
Sign up to set email alerts
|

A U‐shaped association between baseline neutrophil count and COVID‐19‐related mortality: A retrospective cohort study

Abstract: Background Several descriptive studies have reported that higher neutrophil count (NC) may be correlated with poor prognosis in patients with confirmed COVID‐19 infection. However, the findings from these studies are limited by methodology and data analysis. Methods This study is a cohort study. We non‐selectively and consecutively collected a total of 663 participants in a Chinese hospital from January 7 to February 28. Standardized and two‐piecewise Cox regression mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“… 12–14 The relationship between baseline neutrophil count and mortality in COVID-19 is U-shaped with increased mortality risk for both neutropenia and neutrophilia. 37 While neutropenia is a common occurrence in patients with HM, whether depth and duration of neutropenia are associated with outcome in COVID-19 in the HM population is not well studied. Patients with acute leukemia usually have profound and long-lasting neutropenia due to both disease-related and treatment-related factors, so focus on the subpopulation of patients with cancer having leukemia might indirectly describe the role of neutropenia in COVID-19 prognosis.…”
Section: Introductionmentioning
confidence: 99%
“… 12–14 The relationship between baseline neutrophil count and mortality in COVID-19 is U-shaped with increased mortality risk for both neutropenia and neutrophilia. 37 While neutropenia is a common occurrence in patients with HM, whether depth and duration of neutropenia are associated with outcome in COVID-19 in the HM population is not well studied. Patients with acute leukemia usually have profound and long-lasting neutropenia due to both disease-related and treatment-related factors, so focus on the subpopulation of patients with cancer having leukemia might indirectly describe the role of neutropenia in COVID-19 prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Transitional B cells [114], as well as memory B cells [115], all exhibit these trends, with levels strongly correlated with decreased survival. Conversely, massive overactivation of B cells can herald worse outcomes [61], similar to the U-shaped correlation of disease severity and levels of neutrophils [92].…”
Section: Resultsmentioning
confidence: 99%
“…While neutropenia is associated with increased risk and severity of various infections, its effect on COVID-19 outcomes is not well understood. Both low and high neutrophil counts have been linked to higher mortality in COVID-19 [54, 92]. In a multicenter study from Spain including HM patients, neutropenia of less than 500 cells/µL was an independent risk factor for mortality [38].…”
Section: Resultsmentioning
confidence: 99%
“…The table below includes a list of studies which have also found ANC to be significantly associated with survival and severity. Another recent study by Wei et al evaluated neutrophil count as a predictor variable (23). They studied the correlation of baseline neutrophil count (bNC) and neutrophil change rate (NCR) with death.…”
Section: Discussionmentioning
confidence: 99%